2007
DOI: 10.1038/sj.gene.6364402
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to severe streptococcal sepsis: use of a large set of isogenic mouse lines to study genetic and environmental factors

Abstract: Variation in responses to pathogens is influenced by exposure history, environment and the host's genetic status. We recently demonstrated that human leukocyte antigen class II allelic differences are a major determinant of the severity of invasive group A streptococcal (GAS) sepsis in humans. While in-depth controlled molecular studies on populations of genetically wellcharacterized humans are not feasible, it is now possible to exploit genetically diverse panels of recombinant inbred BXD mice to define genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 60 publications
2
54
0
Order By: Relevance
“…Another interesting observation was that, in general, susceptible strains survival was better correlated with bacterial load in blood and spleen than resistant strains. Together, these findings confirm that there is more than one mechanism modulating differential susceptibility or resistance to severe GAS sepsis (Aziz et al, 2007).…”
Section: Variable Susceptibility To Severe Gas Sepsis In Genetically supporting
confidence: 70%
See 4 more Smart Citations
“…Another interesting observation was that, in general, susceptible strains survival was better correlated with bacterial load in blood and spleen than resistant strains. Together, these findings confirm that there is more than one mechanism modulating differential susceptibility or resistance to severe GAS sepsis (Aziz et al, 2007).…”
Section: Variable Susceptibility To Severe Gas Sepsis In Genetically supporting
confidence: 70%
“…Our initial studies (Aziz et al, 2007) demonstrated that there is considerable variability among BXD strains with respect to susceptibility to severe GAS sepsis. To quantify differences among strains in this study, we used three main quantitative traits, namely animal survival, bacteremia, and bacterial dissemination to spleen.…”
Section: Variable Susceptibility To Severe Gas Sepsis In Genetically mentioning
confidence: 99%
See 3 more Smart Citations